De la guerre civile comme vecteur d’émancipation féminine : l’exemple des aristocrates frondeuses (France, 1648-1653) - Sophie Vergnes (Genre & Histoire)
Between 1648 and 1653, Ann of Austria, queen regent of France, had some difficulty in establishing her authority, for the discourse of lawyers and political theoreticians had widely contributed to discredit feminine power since the end of the sixteenth century. At the same time, the Frondeuses from the aristocracy used the discourse in defence of women that had spread among society circles in the 1640s to take part in the civil war. It helped them to justify their military and political interventions despite their supposed “weakness”. The most committed of them wrote during the Fronde several texts (pamphlets, letters) showing themselves as stateswomen, as capable and rightful as their male counterparts. The Grande Mademoiselle, in her Memoirs, claims that same feminine ability but reserves it to women of high birth. She subordinates gender hierarchy to social hierarchy, thus promoting a kind of elitist feminism.